Transforming education with community-developed teaching materials: evidence from direct observations of STEM college classrooms - Rachel Teasdale; Katherine Ryker; Karen Viskupic; C. Doug Czajka; Cathryn Manduca (SpringerOpen, 2020)
Abstract Background The Classroom Observation Project employs direct observations of geoscience teaching across the USA using the Reformed Teaching Observation Protocol (RTOP) to quantify the use of reformed teaching practices. We report on 345 RTOP observations used to evaluate the extent of teaching reform when curricular materials developed as part of the InTeGrate Project (ITG) were used. The InTeGrate Project has published 40 modules of curricular materials that teach geoscience in the context of societal issues and support instructors through guided use of student-centered instructional practices. All ITG materials were developed by teams of instructors, follow a consistent structure, and were evaluated against a project rubric. Results RTOP scores for classes observed when ITG materials were used (ITG; n = 50, M = 54.0) are significantly higher than RTOP scores for classes observed when ITG materials were not used (non-ITG; n = 295; M = 39.8; p < .0001). ITG observations all have RTOP scores in the student-centered (≥ 50) or transitional (31-49) instructional categories, and none in the teacher-centered instructional category (≤ 30), demonstrating that ITG materials support more student-centered teaching in class sessions where they are used. In 33 paired observations of the same instructor teaching with and without ITG materials, mean RTOP scores when teaching with ITG are greater than mean RTOP scores when teaching without ITG (M = 54 and M = 47.1, respectively). Conclusions RTOP observations reveal that more student-centered instructional practices occur in class sessions in which ITG materials are used. There is a small range of RTOP scores when individual ITG activities are used by multiple instructors, suggesting that using ITG materials results in a consistent quality of instruction. The complete absence of teacher-centered instruction when using ITG materials means the materials are a useful resource for practicing reformed teaching methods. The model of the ITG Project in the creation and broad dissemination of ready-made curricula for use in large numbers of classrooms can be replicated to transform teaching and learning in other disciplinary communities.